(3GdOQI GdKejfI aj Mce GdUdGI aj GdSajfIs - (3CMeO GdMehjs
(3ChdgG (B:s
(3hHYO abO QaY Edi SDGd eGbhdce QVi Gddg Yfce ai QLd Udi ai SajfI eQHhWI Ydi TGWF GdHMQ s
(3BNQgG (B:s
(3hEf cGf GdSDGd eaQhVkG ai UdGI GdaQV hGddg GdgGOi ddSOGO s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3abg Mfai (B1166) s
Keywords: (3Gdabg GdMfajs